Educational Research in Latin America - Akkari, Abdeljalil; Perez, Soledad (Education Policy Analysis Archives, 1998)
The present paper consists of four primary sections. First, we describe the historical context of educational research in Latin America. In the second section, we focus on various theoretical frameworks that are applied to educational research in the region. We identify the main institutions involved in this research in the third section. Finally, in conclusion we offer suggestions that we consider to be of greatest priority for the future of educational research in Latin America.